Analisis Tingkat Penerapan Good Agricultural Practices (GAP) Terhadap Usaha Tani Sawi Di Kecamatan Delta Pawan - Akbar, Wahris Tursadi; Maswadi, Maswadi; Kurniati, Dewi Kurniati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Good Agricultural Practice, or GAP for short, is a set of guidelines for good and correct mustard plant cultivation that emphasizes safety, health, and community welfare while aiming for high productivity, high-quality products, maximum profit, and environmental friendliness. In this instance, the author wishes to investigate "Analysis of the Level of Implementation of Good Agricultural Practices on Mustard Farming in Delta Pawan District, Ketapang Regency" in light of the aforementioned statement. The goal of this study was to ascertain, through analysis, the extent to which Good Agriculture Practices (GAP) are being used to mustard cultivation in Noble New Village and the factors that impact the decision to implement GAP. On the cultivation of mustard in Noble New Village, as well as the elements that impact the decision to implement Good Agriculture Practices (GAP) in this area.The sociodemographics of the degree of Good Agricultural Practice (GAP) application and the factors influencing farmers' decisions to implement GAP mustard farming in Mulia Baru village, Ketapang Regency, were analyzed using binary logistic regression and descriptive statistical analysis of percentage. According to the study's findings, age and farming experience are the two factors that significantly influence farmers' decisions to adopt GAP, while land acreage, family dependents, and educational attainment are not major factors.